(untitled) (Globalization and Business, 2023)
For several decades, pension systems across the world have been undergoing reforms. The main reasons for this are demographic changes and increasing life expectancy. As life expectancy increases and the birth rate decreases, more people retire than are added to the workforce. To make these reforms more effective and ensure that they are based on the best benchmarks, the European Union (EU) has introduced the Open Method of Coordination (OMC) in the field of pensions. Pension system reform is on its way in Georgia since 2019, January. OMC evaluates pensions systems in terms of the three main objectives: adequacy, sustainability, and modernization of pensions. Our methodology is based on multivariate statistical analysis, and employs synthetic indicators for adequacy objectives, in case of Georgia and 27 EU countries, in the years 2010, 2015 and 2018. The article contributes to the existing literature on pension reforms through investigation of the convergence of EU27 and Georgia pension systems in terms of one of the OMC objectives, in order to evaluate the adequacy of the pension systems.